The Impact of Disasters on Public Health from the Perspective of Residents of Sheberghan City - Hamidi, Enayatullah (Journal of Natural Sciences – Kabul University, 2026)
This research aims to examine the impact of disasters on public health from the perspective of residents in Sheberghan City. Based on standard deviation calculations, a sample of 572 individuals was selected using an accessible random sampling method. Data were collected using a researcher-made questionnaire and the General Health Questionnaire (GHQ-28). The data were analyzed using descriptive and correlational methods via SPSS version 27. The results indicated that accidents have a negative correlation of -65% with public health, and they impact public health by 53%. Furthermore, the accident sub-variables showed an overall negative correlation of -49% and an impact of 48%. The findings suggest that people, particularly those living in areas frequently affected by Disasters such as floods, earthquakes, and droughts, experience more physical and psychological problems.